The Personality of the Protagonist in Sean Penn Movie Script’s Into the Wild - Daulay, M Iqbal Arfyn; Hidayati, Hidayati (Universitas Harapan Medan, 2023)
The objective of the research were to know the personality of Chris McCandless as protagonist by analyzing the evidence from the dialogues and his actions in the movie. And to know what the causing factors of Chris’s personality, the writer used the method in this paper is descriptive-qualitative. The writer focused the dialogues of the movie script, and then analyzing the characteristic using characterization theory based on structuralism and then identified the personality using Big Five Personality by Paul Costa and Robert McCrae. The writer finds out that final result about the personality and the causing factors of Chris McCandless as protagonist. From the analysis, the writer concludes that the personality of the protagonist in Sean Penn Movie’s Into the Wild based on the Big Five Personality is that the protagonist has a high level of Openness to Experience. and the factors that cause the personality trait are the social and cultural factors that influence the personality of the protagonist.